Nada é cem por cento: usos de conhecimentos matemáticos como táticas retóricas nas práticas discursivas de adolescentes atendidos pelo Centro de Referência de Assistência Social CRAS - Viviane Ribeiro de Souza Cabral (2015)
This thesis presents results from a research conducted with 11 adolescents (4 girls and 7 boys), with ages ranging from 13 to 18 years, that were participants of Projovem Adolescente (National Youth Inclusion Program) from a Social Assistance Reference Center (CRAS) in the city of Pedro Leopoldo, during the development of PEAS (Sexual and Emotional Education Program) and other socio-educational activities. The empirical materials were produced from audio recordings and field notes from discursive interactions that happened during the Projovem activities. Such recordings were fully transcribed and, later, analyzed. In the analysis of the interactions we sought for opportunities of numeracy practices appropriation by the young people, taking them, however, as ways of using the language permeated by mathematical relations which are mobilized in the discourse as rhetorical tactics. The theoretical references in which our analysis were based on were Wittgenstein's later works and Certeau's studies about everyday life practice. During the field work we caught the subjects mobilizing mathematical ideas and expressions not exactly to solve what is usually characterized as "mathematical problems" in the school context and even out of it, as we expected in the initial hypothesis. What we observed was the use of those ideas and expressions in the arts of communication seeking to produce certain effects of meaning and marking positions in the interaction that explicitate tensions between different rationalities. Our study wants to contribute to educators, especially the ones that dedicate themselves to mathematics teaching, so they can recognize the legitimacy of the multiple rationalities, which allow us to understand the appropriation processes of socially valued literate practices (including the numeracy practices) as opportunities to learn a little better "what it is to be young with today's youth".